Evidence of Strong Flux Underestimation by Bulk Parametrizations During Drifting and Blowing Snow - Sigmund, Armin; Dujardin, Jérôme; Comola, Francesco; Sharma, Varun; Huwald, Hendrik; Melo, Daniela Brito; Hirasawa, Naohiko; Nishimura, Kouichi; Lehning, Michael (Boundary-Layer Meteorology, 2021)
Abstract The influence of drifting and blowing snow on surface mass and energy exchange is difficult to quantify due to limitations in both measurements and models, but is still potentially very important over large areas with seasonal or perennial snow cover. We present a unique set of measurements that make possible the calculation of turbulent moisture, heat, and momentum fluxes during conditions of drifting and blowing snow. From the data, Monin–Obukhov estimation of bulk fluxes is compared to eddy-covariance-derived fluxes. In addition, large-eddy simulations with sublimating particles are used to more completely understand the vertical profiles of the fluxes. For a storm period at the Syowa S17 station in East Antarctica, the bulk parametrization severely underestimates near-surface heat and moisture fluxes. The large-eddy simulations agree with the eddy-covariance fluxes when the measurements are minimally disturbed by the snow particles. We conclude that overall exchange over snow surfaces is much more intense than current models suggest, which has implications for the total mass balance of the Antarctic ice sheet and the cryosphere.